3D superhydrophobic reduced graphene oxide for activated NO2 sensing with enhanced immunity to humidity - Wu, Jin (2020)
Three-dimensional, superhydrophobic, reduced graphene oxide (RGO) with unique hierarchical structures is synthesized by spark plasma sintering (SPS) in one step for highly selective NO2 detection. Because the oxygenated functional groups in graphene oxide (GO) can be effectively removed to a minimal content (8.8%) by SPS within just 60 s, the formed 3D RGO exhibits superhydrophobicity that endows the fabricated RGO sensor with exceptional immunity to high relative humidity (RH). Specifically, the RGO sensor exhibits a response degradation less than 5.5% to 1 ppm NO2 in a wide temperature range from 25 to 140 °C when the RH increases from 0% to 70%. In addition, an integrated microheater array is employed to remarkably activate the RGO-based NO2 sensor, boosting the sensitivity. The RGO sensor demonstrates the practical capability to detect 50 ppb NO2 and exhibits an extremely low theoretical limit of detection of 9.1 ppb. The good tolerance to environmental variations such as humidity and temperature makes this sensor suitable for reliable application in the Internet of Things (IoT) under ambient conditions. The high NO2 sensing performance is attributed to the unique 3D hierarchical structures with a high specific surface area (850 m2 g−1), a superhydrophobic surface, abundant defect sites and thermal activation.